2015
DOI: 10.1186/s13000-015-0350-9
|View full text |Cite
|
Sign up to set email alerts
|

Histiocytic sarcoma combined with acute monocytic leukemia: a case report

Abstract: BackgroundHistiocytic sarcoma (HS) is a rare malignant tumor. Underlying or associated disorders have been reported in some patients with HS. We herein report a very rare case of HS combined with acute monocytic leukemia (AMoL).Case presentationA 62-year-old man presented with systemic lymph node enlargement and pancytopenia in August 2012. Bone marrow (BM) aspirate showed abnormal hematopoiesis with 3 % blast, but no obvious abnormalities on flow cytometric immunophenotyping. A BM cytogenetic study and fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…HS, which frequently occurs as a secondary event following these hematolymphoid malignancies, has been demonstrated to harbor the same molecular or cytogenetic abnormalities as the primary malignancy. There have been reported cases of HS as a secondary event following the diagnosis of follicular lymphoma , acute monocytic leukemia (AMoL) , hairy cell leukemia , mantle cell lymphoma , MALT type lymphoma , diffuse large B‐cell lymphoma , acute lymphoblastic lymphoma , chronic lymphocytic leukemia , chronic myelomonocytic leukemia , mediastinal germ cell tumors , idiopathic myelofibrosis , and in our case a diagnosis of HS associated with CML. Some of the commonly associated cases compiled from the literature along with their clinical characteristics are summarized in Table .…”
Section: Definition and Epidemiologymentioning
confidence: 73%
“…HS, which frequently occurs as a secondary event following these hematolymphoid malignancies, has been demonstrated to harbor the same molecular or cytogenetic abnormalities as the primary malignancy. There have been reported cases of HS as a secondary event following the diagnosis of follicular lymphoma , acute monocytic leukemia (AMoL) , hairy cell leukemia , mantle cell lymphoma , MALT type lymphoma , diffuse large B‐cell lymphoma , acute lymphoblastic lymphoma , chronic lymphocytic leukemia , chronic myelomonocytic leukemia , mediastinal germ cell tumors , idiopathic myelofibrosis , and in our case a diagnosis of HS associated with CML. Some of the commonly associated cases compiled from the literature along with their clinical characteristics are summarized in Table .…”
Section: Definition and Epidemiologymentioning
confidence: 73%
“…HS is an invasive tumor that responds poorly to treatment and for which there is yet no widely accepted effective therapy (9). Due to the fact that the vast majority of patients are at an advanced stage when they seek medical advice, the survival time is usually <2 years due to the poor response to chemotherapy (10). In recent years, it has been demonstrated that the use of radiotherapy and chemotherapy combined with autologous hematopoietic stem cell transplantation may improve treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoiesis, once viewed as a unidirectional maturation of pluripotent hematopoietic stem cells into specific lineages (such as lymphoid and myeloid), shows considerable plasticity in both normal and malignant hematopoietic cells. Lineage switching has been described in histiocytic sarcoma (HS), Langerhans cell sarcoma or dendritic cell tumor that occur secondary to or synchronous with mediastinal germ cell tumors [ 14 ], lymphoid [ 12 , 13 , 15 22 ], and myeloid malignancies [ 23 , 24 ]. Histiocytic sarcoma cells are derived from bone marrow monocyte precursors [ 25 ], expresses monocyte-macrophage antigens (CD163, CD68, and lysozyme) and lack expression of myeloid antigens such as CD33, CD13 and MPO [ 11 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%